2015
DOI: 10.1590/s2179-975x1415
|View full text |Cite
|
Sign up to set email alerts
|

Daily mass balance of phosphorus and nitrogen in effluents of production sectors of trout farming system

Abstract: Aim: The mass balance has recently been applied in Brazilian aquaculture. In relation to trout farming, few studies have used this methodology as environmental indicator, especially when considering each development stage of fish. The daily mass balance allows an estimate of nutrients discharge, because the sampling effort over 24 hours enables to monitor the variations throughout the day. This study aimed to identify the breeding sector (fingerlings, juveniles and adults) in trout farming contributes with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
2
5
1
1
Order By: Relevance
“…Our data are in accordance with previous studies [3][4][5]8] that estimated ammonia and phosphorus emissions in water tanks from dietary analysis. In particular, we found lower TAN values than those reported by Moraes [5] and Aubin [4], which is a sign of the high feed quality used on the farm involved in our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data are in accordance with previous studies [3][4][5]8] that estimated ammonia and phosphorus emissions in water tanks from dietary analysis. In particular, we found lower TAN values than those reported by Moraes [5] and Aubin [4], which is a sign of the high feed quality used on the farm involved in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in accordance with previous studies [3][4][5]8] that estimated ammonia and phosphorus emissions in water tanks from dietary analysis. In particular, we found lower TAN values than those reported by Moraes [5] and Aubin [4], which is a sign of the high feed quality used on the farm involved in our study. Concerning the p values, our results are in line with those reported by Moraes [5] and are lower than the values reported by Aubin [4] and Dalsgaard [23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In Brazil, although scarce studies performed in trout farming (Caramel et al, 2014;Moraes et al, 2015Moraes et al, , 2016, in bullfrog farming (Borges et al, 2012;Mercante et al, 2014) and in polyculture system (tilapia and shrimps) (Araújo-Silva et al, 2014), showed that environmental indicators can be a useful tool for characterizing the impact, since it allows the comparison of different systems, methods of creation, evaluation of the effectiveness of management practices used in the production system, descriptions of general standards and as reference values (Boyd et al, 2007;Kimpara et al, 2010).…”
Section: Introductionmentioning
confidence: 99%